Cryptorchidism and Reproductive Health: Childhood Issues and their Future Impact - Ogli, Shukrulloyev Fayozjon Zokirjon (Journal of Science in Medicine and Life, 2025)
The frequency of occurrence of cryptorchidism in children is presented. The main methods of diagnostics and treatment of the congenital pathology are considered first of all ultrasound examination, its reliability reaching 88% with palpable testes. Currently, there are about 250 methods of surgical treatment of organ anomalies. The most widely used techniques are Petriwalsky-Shoemaker and Fowler-Stephens one — or two-step orchidopexy. In some cases, they resort to hormonal therapy using chorionic gonadotropin, less often gonadotropin-releasing hormone, but the effectiveness of this therapy does not exceed 15% and depends on the height of the teste in the inguinal canal. With agenesis (aplasia), the teste is replaced with a silicone implant for a psychological and cosmetic defect. When analyzing the results of the correction of pathology in patients, there is a violation of fertility up to 50%, even with the timely release of the testicles.